2018
DOI: 10.1063/1.5010989
|View full text |Cite
|
Sign up to set email alerts
|

Momentum balance and stresses in a suspension of spherical particles in a plane Couette flow

Abstract: Non-Brownian suspension of monodisperse spherical particles, with volume fractions ranging between ϕ = 0.05 and 0.38 and particle Reynolds numbers ranging between Rep = 0.002 and 20, in plane Couette shear flows is investigated using three-dimensional particle-resolved numerical simulations. We examine the effects of volume fraction and particle Reynolds number on the macroscopic and microscopic stresses in the fluid phase. The effective viscosity of the suspension is in a good agreement with the previous empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 71 publications
7
14
2
Order By: Relevance
“…In descending order the lines show the collisional contribution n σxz (orange) defined in (103), the gradient dU x /dz of the mean velocity in the x direction (green) and the particle stresslet averaged over thin ''slices'' of the computational domain parallel to the solid boundaries (blue). Aside from the small statistical fluctuations and the steep rise near the boundaries, caused by particle accumulation near the rapidly moving planes (an effect also reported in [39]), the stresslet and velocity gradients are nearly constant in the gap so that one may define a mixture viscosity µ mix according to (see e.g. [1])…”
Section: An Example: Particulate Shear Flow At Finite Reynolds Numbermentioning
confidence: 87%
See 2 more Smart Citations
“…In descending order the lines show the collisional contribution n σxz (orange) defined in (103), the gradient dU x /dz of the mean velocity in the x direction (green) and the particle stresslet averaged over thin ''slices'' of the computational domain parallel to the solid boundaries (blue). Aside from the small statistical fluctuations and the steep rise near the boundaries, caused by particle accumulation near the rapidly moving planes (an effect also reported in [39]), the stresslet and velocity gradients are nearly constant in the gap so that one may define a mixture viscosity µ mix according to (see e.g. [1])…”
Section: An Example: Particulate Shear Flow At Finite Reynolds Numbermentioning
confidence: 87%
“…As noted after (39), the explicit expressions of all the moments contain derivatives of the Lamb solution potentials evaluated at the particle center. Thus, only the terms containing the zero power of r will survive in the sums.…”
Section: Explicit Expressions For the Momentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective viscosity will thus depend on the particle Reynolds number and will increase significantly when compared with empirical relations (e.g. (2.2)) from the Stokes flow regime (Linares-Guerrero, Hunt & Zenit 2017; Rahmani, Hammouti & Wachs 2018). Based on laboratory measurements in a coaxial-cylinder rheometer, Linares-Guerrero et al (2017) observed that the effective viscosity monotonically increased with increasing particle Reynolds number for suspension volume fractions of .…”
Section: Resultsmentioning
confidence: 98%
“…In the presence of fluid inertia, the effective viscosity of suspensions increases. In the laminar regime, this observation is attributed to multiple effects, including the Reynolds stresses induced by particle fluctuations (Kulkarni & Morris 2008), particle and fluid phase acceleration (Rahmani, Hammouti & Wachs 2018) and anisotropy in microstructure leading to higher effective solid volume fractions (Picano et al 2013). Since viscoelasticity influences both the hydrodynamic forces experienced by particles (Becker et al 1994) and the local microstructure (D'Avino & Maffettone 2015), it is interesting to consider whether and how the increase in effective viscosity is influenced by viscoelastic effects in the carrier fluid.…”
Section: Introductionmentioning
confidence: 99%